多波長フォトメーター観測による降下電子エネルギーパラメーターの推定 - 小野, 高幸; オノ, タカユキ; Ono, Takayuki; 佐竹, 龍介; サタケ, リュウスケ; Satake, Ryusuke; 芳野, 赳夫; ヨシノ, タケオ; Yoshino, Takeo; 平澤, 威男; ヒラサワ, タケオ; Hirasawa, Takeo (国立極地研究所, 1992)
1990年第31次南極地域観測隊により昭和基地において観測された多波長フォトメーターデータより, 酸素原子許容線844.6nm光強度の窒素分子イオンによる427.8nm光強度に対する比を用いて降下電子のエネルギーパラメーター(平均エネルギー並びに全エネルギーフラックス)を求める試みが行われた。データの解析過程において427.8nm光については大気による散乱を受けやすく, 特に発光強度の空間的な変化の激しいオーロラを観測した例などでは, 強いオーロラアーク周辺の領域でも散乱光が測定されてしまい, 見かけ上周辺の降下電子の平均エネルギーが上がってしまう効果が認められた。このような散乱効果を考慮した上で本論文では比較的オーロラ光強度変化の小さいパルセーティングオーロラについては, 844.6nm光強度の427.8nm光強度に対する比を, また発光強度変化の激しいオーロラブレイクアップに伴うアークについては, 844.6nm光強度の670.5nm光強度に対する比を用いた解析手法を提案した。様々なオーロラの事例について解析を行い, これらを過去におけるロケットや人工衛星による直接観測による結果と比較した結果, 定性的には良い一致が見られた。このため上記3波長のオーロラ輝線の強度比は, 降下電子平均エネルギーを推定する際には適した波長であると考えられる。 Average energy and total energy flux of the incident electrons in active auroras are estimated by using the intensity ratio of auroral emissions measured with a multi-channel photometer at Syowa Station, Antarctica, in 1990. To avoid possible ambiguities which are mainly caused by quenching effects on meta-stable species and complex excitation processes, we used intensity ratios of the emissions of allowed transitions such as 844.6nm (OI), 670.5nm (N_21PG), and 427.8nm (N_2^+1NG). Measured intensity ratios were directly compared with a result of model calculation of auroral emissions. The estimated energy parameters in active auroras showed a rapid change of average energy as well as total energy flux of electrons associated with pulsating auroras and intense auroral arcs. Average energy and total energy flux of the auroral electrons determined by the present method were consistent with the result of the previous in-situ observations of precipitating electrons. Our data analyses on active arcs in break-up phase showed that usage of the 427.8nm emission has difficulty due to a scattering effect of the atmosphere. Usage of 670.5nm emission in place of 427.8nm made it possible to evaluate the energy parameters of electrons even in the vicinity of intense auroral arcs. departmental bulletin paper